An Effectiveness of Group Model Coaching for Improving Life Balance Among Youth - Hussein, Mohd Yusof; Omar, Abdul Jalil; Mohamad, Marlina; Abdul Rahman, Ismail (International Journal of Sustainable Construction Engineering and Technology, 2023)
Life imbalanced amongst youth regarding moral, behaviour and personality problems have been discussed in many studies. However, not many of these research articles discussed on effective interventions process to improve the imbalance especially on youth life. Hence, this study offers a methodology on conducting an effectiveness intervention to improvise youth life-balance. A group of 90 youths were selected from a secondary school to participate the intervention process based on their low academic performance. First phase of the intervention was to investigate the imbalanced elements using a modified Wheel of Life which consisted of 8 elements with 10-points scale. During the investigation session, youth are required to shed the modified Wheel of Life based on individual perspective. The coach analysed all the 90 shaded Wheel of Life and found that personality and discipline element has the lowest score. Then, only 9 youth that having lowest score in this element are grouped and proceed to second phase which is called coaching session. In this session, the youth have undergone 5 interaction sessions where the first session is known as ice breaking activity then followed by another 4 interactions coaching sessions using GROUP model approach. The purpose of ice breaking session was to gain rapport amongst youth.  Then during the GROUP model coaching session, a pre and post coaching forms were prepared and filled by the youth to gauge their life balance status. These GROUP model coaching sessions continued until the fourth session. Then, the pre and post coaching forms were analysed to quantify the impact of the coaching sessions on the youth personality and discipline element. For the last phase, the results of these coaching sessions were validated through the interview session with the teachers and parents of the youth. It was found that the average effectiveness percentage of the GROUP model coaching is 72.95%.  It is hope that this study contributes new knowledge on intervention process to improvise youth life balance.